A Glance At Internal And External Qualities Of Kuttanad, White Pekin And Commercial Duck Eggs - Harikrishnan, S.; Ponnuvel , P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A study was carried out to determine the egg qualities of farm fresh Kuttanad and White Pekin duck eggs of the institute and eggs collected from various shops in and around Thrissur district, Kerala. A total of 42 eggs were subjected to evaluate the internal and external quality parameters. The results revealed that there is no significant difference among mean egg weight, shape index and specific gravity. Kuttanad and White Pekin farm fresh eggs showed significantly (P
Keywords: Duck egg; Egg quality traits; Breeds